Influence of Sr addition on structural, dielectric and Raman properties of Na0.5Bi0.5TiO3 ceramics. Issue 173 (23rd July 2016) - Suchanicz, J.; Dutkiewicz, M. E.; Jelen, P.; Handke, B.; Skolowski, M.; Antonova, M.; Sternberg, A.
ABSTRACT: Lead free (Na0.5 Bi0.5 )1-x Srx TiO3 (x = 0, 0.01 and 0.02) ceramics were produced by a conventional solid-state sintering method. X-ray diffraction analysis shows that the obtained samples possess the perovskite structure with rhombohedral symmetry. The microstructure study shows a dense structure, in agreement with the relative density (above 97%). Dielectric analysis revealed the diffuse character of the electric permittivity anomalies and their shift to a lower temperature range after Sr doping of NBT. The Raman spectra are similar for all samples in agreement with the X-ray diffraction data. The possible origin of the observed effects was discussed.